Relationships Between Liver Histopathology with Biochemical Parameters, and Hepatitis B Virus-DNA in Chronic Hepatitis B Infection. - Özdemir, Yusuf Emre; Doğdaş, Esra Salim; Demir, Adile Sevde; Borcak, Deniz; Ünlü, Esra Canbolat; Sezen, Ayşegül İnci; Bayramlar, Osman Faruk; Yaşar, Kadriye Kart (Viral Hepatitis Journal / Viral Hepatit Dergisi, 2023)
Objectives: We investigated the relationship between serum hepatitis B virus (HBV)-DNA levels and biochemical parameters and liver histopathology in patients with chronic hepatitis B (CHB). Materials and Methods: In this single-center retrospective study, treatment-naive hepatitis B e antigen (HBeAg) negative CHB patients between 2015 and 2022 years were included. Results: A total of 316 patients were included. There were significant correlations between the histological activity index (HAI) score and HBV-DNA (r=0.522, p<0.001), alanine aminotransferase (ALT) (r=0.349, p<0.001), aspartate aminotransferase (r=0.414, p<0.001), and fibrosis score (r=0.111, p=0.049). The fibrosis score did not have a significant correlation other than the HAI. Patients with normal ALT levels had higher minimal inflammation (19.6% vs. 4.7%, p<0.001) and mild fibrosis (88.7% vs. 80.4%, p=0.042) than patients with elevated ALT levels. High HBV-DNA (>2,000,000 IU/mL) (60.8% vs. 36.7%, p=0.003) and moderate inflammation (27.6% vs. 13.9%, p=0.042) were higher in patients with ALT >2x upper limit of normal (ULN) than in patients with ALT 1-2xULN. For predicting HAI ≥6, the area under the receiver operating characteristics (AUROC) values of HBV-DNA (cut-off: 33,427) and ALT (cut-off: 40.5) were 0.726 and 0.664, respectively. For predicting ≥F2 the AUROC values of HBV-DNA (cut-off: 721,062) and ALT (cut-off: 44.5) were 0.624 and 0.597, respectively. Conclusion: This study revealed positive correlations between laboratory parameters and HAI score, but not with fibrosis score. In addition, HBV-DNA and ALT showed poor diagnostic performance in predicting ≥F2. Therefore, while viral load and ALT are useful predictors of hepatic inflammation, the role of these markers in predicting fibrosis remains unclear.